A new mammal track from the Laramie Formation (Maastrichtian) at the Fossil Trace locality, Golden, Colorado. (October 2017) - Lockley, Martin G.; Matthews, Neffra A.; Breithaupt, Brent
Abstract: A previously unknown and morphologically distinct pentadactyl mammal track was recovered from the Upper Cretaceous (Maastrichtian) Laramie Formation at the Fossil Trace site, a National Natural Landmark which is the type locality for Schadipes crypticus, the only named mammal track known from North America. The track is different, and larger than S. crypticus, and thus is evidence of a diversity of mammal trackmakers at this site. Although Cretaceous mammal tracks are very rare, preliminary indications are that those currently known are all morphologically distinct and therefore indicative of a global diversity of different trackmakers, as the body fossil record suggests. Lack of well-preserved mammal trackways with morphologically distinct manus and pes footprints hampers efforts to name diagnostic ichnotaxa.